Antiarrhythmic Mechanisms of Chinese Herbal Medicine Dingji Fumai Decoction. (20th March 2020) - Liang, Bo; Zhou, Yan; Fu, Ling; Liao, Hui-Ling
Abstract : Background . Dingji Fumai decoction (DFD) is used to treat ventricular arrhythmia, and it has provided a very good curative effect. However, its cellular electrophysiological mechanism is unknown. Methods . Electrocardiogram was recorded, and oxidative stress response and ion-channel-related molecules were detected in rats with barium chloride- and aconitine-induced ventricular arrhythmia. Moreover, whole-cell patch-clamp assay was used to investigate the inhibitory effect of DFD on Nav1.5 in Chinese hamster ovary cells. Results . DFD prolonged the occurrence time and shortened the duration of ventricular arrhythmia, decreased the malondialdehyde and increased the superoxide dismutase, and alleviated the activation of Na + -K + -ATPase and connexin-43. DFD suppressed Nav1.5 dose-dependently with an IC50 of 24.0 ± 2.4 mg/mL. Conclusions . The clinical antiarrhythmic mechanisms of DFD are based on its antioxidant potential, alleviation of Na + -K + -ATPase and connexin-43, and class I antiarrhythmic properties by suppressing Nav1.5 dose-dependently with an IC50 of 24.0 ± 2.4 mg/mL.